Data Storage: Functional Applications of Future Data Storage Devices (Adv. Electron. Mater. 5/2021). (12th May 2021) - Yang, Jia‐Qin; Zhou, Ye; Han, Su‐Ting
Abstract : In article number 2001181, Jia‐Qin Yang, Ye Zhou, and Su‐Ting Han provide a perspective on the development of future data storage devices. Different memory techniques, operating schemes, and applications in future computing scenarios are reviewed.